Trials under security cases / Hasnol Mohd. Nasir - Mohd. Nasir, Hasnol (Faculty of Law, 1986)
There has been a marked increase in the number of cases under the Internal Security Act and the Emergency Regulations that has consequently brought this area of discussions into sharp focus in the eyes of the public. It is about this the writer therfore seeks to provide a brief, compact and clear enunciation of the issues that involved the trial in any security cases which are different with any offences under the Penal Code nor under Evidence Act. In other words for offences cOl1lTlitted under security cases the procedure ot trial and gathering of evidence is a different from the ordinary trials. Chapter I serve as an introduction chapter under which the writer sets out the history of Emergency in Malaysia. Discussion on preventive detentions and emergency powers granted to the executive listed under the constitutional provisions are also discussed under this chapter. Essential (Security Cases) (Amendment) Regulations 1975 are discussed under chapter II. In this chapter the writer discusses certain areas which are proclaimed as security areas by the Yang Dipertuan Agong and also the implementation of the Security Cases Regulations in Malaysia.